Tunica Vaginalis Flap Versus Inner Preputial Dartos Flap as Waterproof Layer for Proximal Staged Hypospadias Repair: A Comparative Study - Zakaryia Yahya Moosa1 , Yousuf Mohammed AL-hallak2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Hypospadias is an abnormality of anterior urethral and penile development in which the urethral opening is ectopically located on the ventral aspect of the penis proximal to the tip of the glans penis, which, in this condition, is splayed open. [1] The urethral opening may be located as far down as in the scrotum or perineum. The penis is more likely to have associated ventral shortening and curvature, called chordee, with more proximal urethral defects. Aim: To compare the outcome of using tunica vaginalis flap to dartos flap in proximal two stage hypospadias repair in reducing post-operative complication (dehiscence and fistula). Materials and Methods: In the defined period of January 2015 to June 2018, 47 male patients with clinical diagnosis of penoscrotal hypospadias, The age of the patients range from 2 years to 10 years, All these cases were managed in 2 stages repair with buccal mucosal graft, with either tunica vginalis flap (group A) (25 cases) , or preputial dartos flap (group B)(22 cases) as a second cover over new tubularized urethra. We compared between these two groups regarding complications rate. Result: we observed that tunica vaginalis flap was better than dartos flap (although it was statistically non significant p value 0.214 > 0.05) specifically in fistula formation. Conclusion: we observed that tunica vaginalis flap had excellent outcome when used as a second layer over the neourethral suture line in term of decrease the fistula rate and wound dehiscence because of its good vascular features